Establishing the Muslim village - Hosein, Imran Nazar; One Islam Publications (N.S.W, Australia : One Islam Productions, 2006)
A talk on establishing a muslim village, the practices as a muslim, includes a social life as a muslim
Title from title screen
Lecturer : Sheikh Imran Hosein
Keywords: Islam -- Customs and practices; Religious life -- Islam